Supramolecular Assemblies: Supramolecular Protein Assembly Retains Its Structural Integrity at Liquid–Liquid Interface (Adv. Mater. Interfaces 4/2020). Issue 4 (21st February 2020) - Sarker, Mridul; Lee, Hwankyu; Gonçalves, Rui A.; Lam, Yeng Ming; Su, Haibin; Lim, Sierin
Abstract : Proteins are traditionally thought to denature at interfaces (liquid‐liquid or solid‐liquid). However, all studies have been done mostly using either monomeric ones or small globular proteins. In article number 1901674, Haibin Su, Sierin Lim, and co‐workers find that supramolecular protein assemblies, such as self‐assembling protein cages of nanometer size, remain intact at oil‐water interface. Balancing of forces that keep the assemblies together and those that are experienced at the interface is key.